Direct impact of psoriasis on gingival crevicular fluid levels of VEGF-A in periodontitis patients: a mediation analysis - Jiménez, Constanza; Fernández, Javier; Rodríguez, Camila; Mancilla, Juan Felipe; Pellegrini, Elizabeth; Hernández, Marcela; Valenzuela, Fernando; Fernández, Alejandra (Frontiers in Immunology, 2024)
Emerging evidence suggests that psoriasis and periodontitis are linked via systemic inflammation. However, the role of angiogenesis as an additional connecting mechanism between these diseases remains unclear. This case control study explored the effect of psoriasis on the gingival crevicular fluid (GCF) levels of vascular endothelial growth factor A (VEGF-A) in patients with different stages of periodontitis. Thirty-one patients with psoriasis (P) and thirty healthy controls (C) underwent physical and intraoral evaluations, with diagnoses confirmed by dermatologists and periodontists. GCF VEGF-A was measured using a multiplex-bead immunoassay. Statistical analyses included Fisher exact tests, Student's T-tests, linear regression models, and mediation analyses. Results showed that psoriasis patients had significantly lower GCF VEGF-A levels compared to controls (p=0.008). Psoriasis was negatively associated with GCF VEGF-A (p=0.006), while severe periodontitis was positively associated with GCF VEGF-A levels, regardless of tobacco use (p=0.027). Further analyses revealed that severe periodontitis significantly increased GCF VEGF-A levels only in the C group (p=0.038), but not in psoriasis patients (p>0.610). Mediation analyses confirmed a significant direct and total effect of psoriasis on GCF VEGF-A (p>0.002), with no significant indirect effect through periodontitis (p=0.699). In conclusion, psoriasis and severe periodontitis are associated with GCF levels of VEGF- A in opposite and independent ways. In subjects with psoriasis, the impact of the dermatosis is direct with no mediation from periodontitis.